The Role of Knowledge Management in Achieving the Sustainable Competitive Advantage for Secondary Schools in Riyadh City - Almohammadi, Nouf Hameed (Journal of Educational and Psychological Sciences, 2025)
The study aimed to identify the role of knowledge management in achieving sustainable competitive advantage in secondary schools in northern Riyadh from the perspective of principals and teachers, examining its contribution to total quality, administrative flexibility, and cost efficiency. It also explored potential differences based on profession, years of service, and the number of training courses, while addressing the challenges facing knowledge management and proposing mechanisms to enhance its effectiveness. A descriptive survey methodology was employed, using a 50-item questionnaire administered to a sample of 109 principals and teachers. The findings revealed a high level of agreement on the role of knowledge management in achieving total quality and administrative flexibility, with a mean score of 2.48 out of 3.00, while agreement on cost efficiency was moderate, with a mean of 2.20. Participants also expressed strong agreement on the presence of challenges hindering knowledge management (mean 2.44) and on the proposed mechanisms for strengthening its role (mean 2.68). Statistically significant differences were found in total quality in favor of teachers, whereas no significant differences emerged for the other dimensions, challenges, or mechanisms across the studied variables. The study recommended promoting the application of quality standards, fostering knowledge sharing and experience exchange, establishing incentive systems, providing supportive technological environments, designing specialized training programs, ensuring clarity of strategic goals and staff involvement, and allocating dedicated budgets for knowledge management to secure sustainable competitive advantage.
Keywords: Role; Knowledge Management; Sustainable Competitive Advantage; Secondary Schools